Effect of mindfulness yoga programme MiYoga on attention, behaviour, and physical outcomes in cerebral palsy: a randomized controlled trial. (4th June 2018) - Mak, Catherine; Whittingham, Koa; Cunnington, Ross; Boyd, Roslyn N
Abstract : Aim: To investigate the efficacy of an embodied mindfulness‐based movement programme (MiYoga), targeting attention in children with cerebral palsy (CP). Method: Total number of participants 42, with 24 boys (57.1%) and 18 girls (42.9%); mean age 9y 1mo, SD 3y; Gross Motor Function Classification System levels I=22, II=12, III=8) and their parents were randomized to either MiYoga ( n =21) or waitlist comparison ( n =21) groups. The primary outcome was attention postintervention measured by the Conners' Continuous Performance Test, Second Edition (CCPT). Secondary outcomes included parent and child mindfulness, child quality of life, parental well‐being, child executive function, child behaviour, child physical measures, and the parent–child relationship. Results: Children in the MiYoga group demonstrated significantly better attention postintervention than the waitlist comparison group, with lower inattention scores on the hit reaction time standard error ( F 1, 33 =4.59, p =0.04, partial eta‐squared [ η p 2 ]=0.13) variable and fewer perseveration errors ( F 1, 33 =4.60, p =0.04, η p 2 =0.13) on the CCPT. Intention‐to‐treat analysis also revealed that sustained attention in the MiYoga group was significantly better than in the waitlist comparison group postintervention ( F 1, 37 =5.97, p =0.02, η p 2 =0.14). Parents in the MiYoga group demonstrated significantly decreased mindfulness (Mindfulness Attention Awareness Scale; F 1, 33 =10.130, p =0.003, η p 2 =0.246). Interpretation: MiYoga offers a lifestyle intervention that improves attention in children with CP. MiYoga can be considered as an additional option to standard rehabilitation to enhance attention for children with CP. What this paper adds: MiYoga, an embodied mindfulness‐based movement programme, can enhance attention (more attentive and consistent performance) in children with cerebral palsy. MiYoga had no significant effect on physical functioning. What this paper adds: MiYoga, an embodied mindfulness‐based movement programme, can enhance attention (more attentive and consistent performance) in children with cerebral palsy. MiYoga had no significant effect on physical functioning. This article is commented on by Rinehart, Jeste, and Wilson on pages856–857 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.